Developing integrated digital printing learning module on thematic lessons for students with mental retardation - Nurjaya, Nurjaya; Salwa, Dian Fatimatus; Nabil, Nisrina Hasna'; Wibowo, Muhammad Yusuf; Istighfaroh, Maulina (International Journal on Education Insight, 2022)
Education is important for every human because we can think and have a lot of knowledge for life. Children with special needs for mental retardation have problems or problems during the learning process, one of them is thematically. The Research and Development (R&D) research method is carried out by studying research related to the product, developing a product based on these findings, testing it in the field in a setting, and revising it to correct deficiencies found at the proposed testing stage. The development model used in this research is the Analyze, Design, Develop, Implement, and Evaluation (ADDIE) model. Analysis of the needs of mentally retarded students found the competencies need to be improved are the ability to read, write and count or commonly called calistung. This model will develop a learning media. The learning media that will be developed are in the form of modules intended for students with mental retardation in grade 2 elementary school (SD). The module was then developed into a learning module that is integrated with digital media. This development resulted in a product in the form of a printed module of the hypercontent type of digitally integrated thematic subject for grade 2 students of the Elementary School with Special Requirements. This module can help the teaching and learning process that is suitable to be applied to mentally retarded children.